Transcriptomic Analysis of Chilled Tan Lamb - CHEN Xueyan, YANG Bo, LUO Ruiming, ZHANG Qian, WANG Jinxia, LI Rong, HU Lijun (Shipin Kexue, 2024)
This study was performed in order to uncover the molecular mechanism by which postmortem glycolysis affects meat quality traits for the purpose of promoting the research and development of prediction technologies for the quality change of chilled Tan lamb and promoting the improvement of its processing, storage and transportation technologies. High-throughput sequencing technology was used for transcriptome sequencing and analysis of the hind leg meat from Yanchi Tan lambs after 0, 4 and 8 days of chilling. The results showed that the differential expression genes (DEGs) were mainly enriched in cellular amide metabolism, ATP metabolism, skeletal muscle contraction and ribosomes and involved in glycolysis, ribosomes and the p53 signaling pathway, and these DEGs constituted a key part of muscle cell function. The phosphofructokinase (PFKM), glyceraldehyde-3-phosphate dehydrogenase (GADPH), phosphoglycerate mutase 2 (PGAM2), enolase 3 (ENO3) and pyruvate kinase (PKM) genes were the core genes involved in the glycolytic metabolism of Tan lambs, which changed meat quality mainly by affecting the structure of muscle fibers, the degradation degree of structural proteins, the activity of glycolytic enzymes, the production of ATP and the activity of complexes.